Analisis Pelatihan Kerja, Komunikasi, dan Pengembangan Karir Terhadap Kinerja Karyawan PT. Indomarco Prismatama Cabang Medan - Nadra Nadhilah; Eli Delvi Yanti (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to find the influence of job training, communication, and career development on the performance of employees of PT Indomarco Prismatama Medan Branch. This type of research is causal research with a quantitative approach. The number of samples in this study is 73 employees. The data collection technique used is a questionnaire technique. This study uses quantitative data processed with SPSS 25.0 with a multiple linear regression model. The results of the study show that partial and simultaneous job training, communication, and career development have a positive and significant effect on the performance of employees of PT Indomarco Prismatama Medan Branch. The results of the t-test showed that the job training had a regression value of 0.223, a tcal value = 2.559 and a significant = 0.000. Communication has a regression value of 0.414, has a tcal value = 4.747 and significant = 0.000. Career development has a regression value of 0.255 and a calculation value of 3,682. The results of the determination coefficient test of 91.6% of employee performance can be explained and obtained from the variables of job training, communication, and career development while the remaining 8.4% is influenced by other factors.